Dalam ANALYSIS OF ISSUES AND PROBLEMS OF REGIONAL ECONOMIC DEVELOPMENT IN KUDUS DISTRICT - Alfaris, Muh Rafi (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
In Indonesia's economic development, there are several issues and challenges that need to be addressed to achieve the desired progress. The following paper will explore in more depth the issues and problems of economic development that occur in Kudus Regency. The study conducted in this research uses the literature research method. The results of this research explain that first, national development aims to improve welfare and build a developed country with community participation and government support. However, development failures often stem from structural problems that require comprehensive solutions. Second, economic development in Kudus Regency is influenced by the Covid-19 Pandemic, SDGs, global economic crisis, environmentally friendly economy, natural disasters, and green space control. Third, the solution to improving economic development in Kudus Regency involves granting special autonomy to the regions. Economic diversification, job training, infrastructure improvement, innovation, and transparency in development policies are the key steps to achieve the goal.